2008
DOI: 10.1370/afm.843
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Depression and Hypertension Treatment: A Pilot, Randomized Controlled Trial

Abstract: PURPOSE We wanted to examine whether integrating depression treatment into care for hypertension improved adherence to antidepressant and antihypertensive medications, depression outcomes, and blood pressure control among older primary care patients. METHODSOlder adults prescribed pharmacotherapy for depression and hypertension from physicians at a large primary care practice in West Philadelphia were randomly assigned to an integrated care intervention or usual care. Outcomes were assessed at baseline, 2, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 42 publications
4
132
1
5
Order By: Relevance
“…The integrated care manager worked individually with patients to address the factors involved in adherence presented in our conceptual model, adapted from Cooper and colleagues, 26 and previously published. 27,28 In our conceptual model, the patient-level factors resulting in nonadherence included depression, chronic medical conditions, function, cognition, social support, cost of medications, side effects, and past experiences with medications. Patient-level factors were addressed through a variety of activities that included in-person sessions, telephone contacts, and collaborating with the physician.…”
Section: Interventionmentioning
confidence: 99%
“…The integrated care manager worked individually with patients to address the factors involved in adherence presented in our conceptual model, adapted from Cooper and colleagues, 26 and previously published. 27,28 In our conceptual model, the patient-level factors resulting in nonadherence included depression, chronic medical conditions, function, cognition, social support, cost of medications, side effects, and past experiences with medications. Patient-level factors were addressed through a variety of activities that included in-person sessions, telephone contacts, and collaborating with the physician.…”
Section: Interventionmentioning
confidence: 99%
“…Данные литературы об антигипертензивных эффектах СИОЗС немногочисленны и достаточно противоречивы [13,14]. Предполагается, что исполь-зование Эс может обеспечивать блокаду пресинапти-ческих серотониновых рецепторов, увеличивать выделение и накопление серотонина в синаптиче-ской щели, и, как результат, стабилизирует функцио-нирование серотонинергической системы [11].…”
Section: материал и методыunclassified
“…For example, Lin et al and others have previously shown that depression care management has the potential to improve multiple symptom domains. [8][9][10] Further, patient populations with multiple morbidities and depression may be more responsive to general self-management interventions than are populations with no depression and fewer medical conditions. 11,12 Thus, there seems to be little doubt that care management attending to depression and other conditions has the potential to improve several health outcomes for both conditions.…”
Section: Agency For Healthcare Research and Quality (Ahrq)mentioning
confidence: 99%